Organization of international market introduction: Can cooperation between central units and local product management influence success - Antje Baumgarten; Cornelius Herstatt; Claudia Fantapié Altobelli (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2006)
When organizing international market introductions multinational companies face coordination problems between the leading central organizational unit and local product management. Based on the assumption that international market introductions are initiated and managed by a central unit we examine the impact of cooperation between the central unit and local product management on success. Our survey of 51 international market introductions reveals that the quality of the cooperation with local product management indeed has a positive influence on success. Yet cooperation itself is not sufficient - to make international market introductions successful local product management needs to be actively involved in the decision making process as well.
Keywords: 650